An early-stage 3D fibroblast-featured tumor model mimics the gene expression of the naïve tumor microenvironment, including genes involved in cancer progression and drug resistance - Costabile, Francesca; George, Subin; Facciabene, Andrea; Filaci, Gilberto; Mastrogiacomo, Maddalena (Frontiers in Oncology, 2025)
IntroductionThe tumor microenvironment (TME) plays a crucial role in cancer progression, yet the interactions between tumor cells and stromal components, such as fibroblasts, remain poorly understood. Traditional two-dimensional (2D) culture models fail to accurately replicate the complexities of the TME, hindering progress in cancer research and drug development.MethodsThis study presents a novel 3D spheroid model, generated using the hanging drop system, that incorporates both tumor cells (B16F10 mouse melanoma) and fibroblasts (NIH/3T3), and aimed at simulating the early-stage TME.ResultsWe demonstrate that fibroblasts are essential for ECM deposition, which is absent in spheroids composed only of tumor cells. Co-cultured spheroids exhibited a more organized structure, enhanced ECM deposition (type-VI collagen), and more closely resembled the morphology of native tumors compared to monocultures. RNA sequencing analysis revealed that the gene expression profile of B16F10–NIH/3T3 spheroids closely matched that of in vivo tumors, with 693 genes involved in critical pathways such as “pathways in cancer” and those linked to drug resistance.DiscussionThese findings highlight the importance of fibroblast inclusion in 3D models to replicate the genetic and structural features of the TME. Our spheroid system provides a more accurate representation of early tumor stages and offers a promising platform for drug screening, reducing the need for in vivo models by allowing the selection of the most effective compounds for further testing. This work underscores the potential of 3D culture systems in advancing our understanding of tumor biology and improving the precision of cancer therapeutics.